Correction: Adipic acid production from lignin. Issue 8 (26th July 2022) - Vardon, Derek R.; Franden, Mary Ann; Johnson, Christopher W.; Karp, Eric M.; Guarnieri, Michael T.; Linger, Jeffrey G.; Salm, Michael J.; Strathmann, Timothy J.; Beckham, Gregg T.
Abstract : Correction for 'Adipic acid production from lignin' by Derek R. Vardon et al., Energy Environ. Sci., 2015, 8, 617–628, ; https://doi.org/10.1039/C4EE03230F .